Assessment of Traffic Policemen Exposure To Benzene by Using Trans, Trans-Muconic Acid Biomarker in Ahvaz City, Iran - Neisi Abdolkazem; Mahmoudi Parviz; Kayedi Neda; Behroozi Hamid (Journal of Cancer Genetics And Biomarkers, 2020)
Benzene is known as an environmental and industrial pollutant. One way to check the amount of exposure to benzene is to measure its metabolites in the urine. Trans, Trans-Muconic Acid which is one of its metabolites is also as a biological indicator of exposure to benzene. In this study, the relationship between the amount of this biomarker and the environmental benzene concentration was investigated in two groups of policemen working outdoors in the traffic-congested areas and indoor in the same area. The results showed that the highest amount of benzene was in Salman Farsi Station at 4.44 ppm. At the same time, the biomarker measured in the urine showed 127.20 μg / L, which was the highest amount. In addition, the amount of benzene in the outdoor was approximately 3 times more than indoor and the amount of biomarker measured in outdoor employees was two times more than indoors ones. In general, wherever there was more benzene, the biomarker would also show a higher amount.
Keywords: Benzene